Exploring Small and Medium Scale Manufacturing Firms and Quality Management of Medicinal Material Supply in a Developing Economy: The Ghanaian Perspective - Twumasi, Juliet; Kyeremeh, Evans; Yankeyera, Benedict Owusu (International Journal of Economics, Business and Management Studies, 2021)
The quality of herbs used to make herbal medicinal products largely influences the safety and effectiveness of these herbal treatments. It is therefore important to investigate the extent to which manufacturers are ensuring the quality supply of herbal medicine used in production of herbal medicine. This study examines how small and medium scale manufacturers assure the quality and continual improvement of the raw materials (raw materials) used for production of medicinal products in a developing economy, the state of Ghana, and the methods used by the company. The study adopted exploratory research design. Using interview quide with open ended questions, data was collected from 88 respondents (small and medium scale manufacturers and their representatives). The data was analysed using NVivo 11. Findings of the study indicated that herbs were collected from the wild (forest), physical inspection of the herbs and best manufacturing practices, good relationship management or collaboration were measures used to promote quality of raw material supply. Also, proper documentation or recording of processes and quality measures do not have much attention or acceptance among Traditional Medicine Practitioners (TMPs).